Volume 6: Turbomachinery, Parts A, B, and C 2008
DOI: 10.1115/gt2008-50196
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Turbine Tip Clearance on Gas Turbine Performance

Abstract: There are many different sources of loss in gas turbines. The turbine tip clearance loss is the focus of this work. In gas turbine components such as compressor and turbine the presence of rotating blades necessitates a small annular tip clearance between the rotor blade tip and the outer casing. This clearance, although mechanically necessary, may represent a source of large loss in a turbine. The gap height can be a fraction of a millimeter but can have a disproportionately high influence on the stage effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 13 publications
1
21
0
Order By: Relevance
“…To investigate the effect of tip leakage flow through the clearance gap between rotor blade and the shroud, LES simulations were conducted for two values of tip clearance using the finest grid, Grid C. For the first case, a large tip clearance of 3.39 mm was used, which is equivalent to 16% of the rotor chord. The geometry was then revised for the second case to reduce the tip gap to 0.62 mm, resulting in a realistic 3% tip clearance Booth et al [12], Bringhenti and Barbosa [13] with respect to the rotor chord. Figure 15 compares the instantaneous velocity magnitude contours obtained for the two cases in the middle of the rotor section in a plane normal to the stream-wise direction.…”
Section: Effect Of Tip Clearancementioning
confidence: 99%
See 1 more Smart Citation
“…To investigate the effect of tip leakage flow through the clearance gap between rotor blade and the shroud, LES simulations were conducted for two values of tip clearance using the finest grid, Grid C. For the first case, a large tip clearance of 3.39 mm was used, which is equivalent to 16% of the rotor chord. The geometry was then revised for the second case to reduce the tip gap to 0.62 mm, resulting in a realistic 3% tip clearance Booth et al [12], Bringhenti and Barbosa [13] with respect to the rotor chord. Figure 15 compares the instantaneous velocity magnitude contours obtained for the two cases in the middle of the rotor section in a plane normal to the stream-wise direction.…”
Section: Effect Of Tip Clearancementioning
confidence: 99%
“…Booth et al [12] found that the tip clearance of 1% results in 1-3% loss in turbine stage efficiency. By using a validated tip clearance model, Bringhenti and Barbosa [13] showed that the reduction in tip clearance allows for engine operation at lower temperatures because of improved efficiency. Other relevant studies have utilized idealized models for quantifying heat transfer and losses associated with tip clearance [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…They found that increased tip clearance heights in the tip regions of two adjacent blades are blame for the larger clearance loss of the centre blade. Effects on turbine tip clearance on gas turbine performance studied by Cleverson Bringhenti and Joao Roberto Barbosa [9]. They observed that the tip clearance have very well affect on its performance and occurs losses.…”
Section: Tip Clearance Flowmentioning
confidence: 99%
“…6 And with further researches, a relationship was discovered by researchers that the decrease of the tip clearance reduces the fuel consumption of the engine at a given working point, as well as the working temperature. 7 Furthermore, if the tip clearance is too big, it will not only decrease the efficiency of the engine but also consume more fuel and even cause a surge. 8 On the contrary, the decrease in tip clearance can reduce the working medium leakage and the loss of the end wall, so as to improve the engine performance.…”
Section: Introductionmentioning
confidence: 99%